Yield and protein gaps in barley: Quantifying nitrogen and sulfur contributions - Gomez, Federico (2026)
Malting barley requires management strategies that simultaneously achieve a high yield and grain protein concentration meeting brewing industry requirements, yet the impacts of nitrogen and sulfur limitations on these variables remain unclear. Yield and protein gaps under rainfed conditions have not been quantified or nutritionally decomposed for barley at the farm scale. This study aimed to i) quantify yield and grain protein gaps in malting barley, ii) evaluate the contribution of N and S to these gaps, iii) examine the relationship between yield and protein gaps, and iv) analyze the relationship between yield, grain protein, and their respective gaps with crop N uptake. Forty-two on-farm experiments were conducted in the central Pampas region of Argentina, with N and S fertilization treatments in a randomized complete block design. These experiments, combined with crop modeling (APSIM), were used to estimate yield potential (Yp), water-limited yield potential (Yw), actual yield (Ya), yield gap (Yg = Yw - Ya), actual grain protein concentration (Pa), and protein gap (Pg = Pi - Pa, where Pi is the 11 % average industrial protein requirement). Mean Yg represented 27.6 % of Yw and was mainly due to N limitation (97.6 % of cases), while S limitation was less frequent (< 23.5 %). Pa was consistently below the 11 % industry requirement. Mean Pg was 26.5 % of Pi and was also mainly due to N limitation. The association between Pg and Yg was weak. Crop N uptake influenced both gaps, with higher N requirements needed to achieve Pi than to maximize yield. This study demonstrates that optimizing N management is essential for closing yield and protein gaps in malting barley in the Pampas, whereas S limitation is less frequent. Future research should integrate the effects of multiple stressors (nutrients, water, and temperature) on yield and protein gaps.